Estimating Current Distributions in Power Semiconductor Dies Under Aging Conditions: Bond Wire Liftoff and Aluminum Reconstruction; IEEE Transactions on Components, Packaging, and Manufacturing Technology; Vol. 5, iss. 6 - Tien Anh Nguyen; Lefevre S. Stefan; Joubert P.-Y. Pierre-Yves; Labrousse D. Denis; Bontemps S. Serge (2015, 2015)
Title screen